Legumes as an alternative protein source in plant-based foods: Applications, challenges, and strategies - Xin Zhang; Zhaonan Zhang; Ao Shen; Tianyi Zhang; Lianzhou Jiang; Hesham El-Seedi; Guohua Zhang; Xiaonan Sui (Current Research in Food Science)
Since animal proteins may pose a threat to the global environment and human health, the development of alternative proteins has become an inevitable trend in the future. Legumes are considered to be one of the most promising sources of sustainable alternative animal proteins. Legume proteins are considered to exhibit excellent processing properties, including emulsification, gelation, and foaming, which have led to their widespread use in the food industry. Moreover, legume proteins are not only taken as substitutes for meat proteins, they also play an essential role in novel plant-based foods (meat, dairy, fermented food, and fat). However, there are few comprehensive overview studies on the application of legume proteins in plant-based foods. Therefore, this review provides a general overview of the main sources, functional properties, and applications in plant-based foods of legume proteins. In addition, challenges to the application of legume proteins in plant-based foods and specific strategies to address these challenges are presented. The review may provide some references for the further application of legume proteins in novel plant-based foods.